The conservation treatment of a contemporary collaged sculpture by Jiří Kolář (1914-2002) - Jessica Crann (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
A collaged sculpture of an apple by the Czech artist Jiří Kolář, dated 1972 was presented for conservation. The sculpture suffered from structural damage caused by external factors and ingrained surface dirt. The ethical implications raised in conserving a contemporary artwork were an important aspect and subsequently an understanding of the materials and structure, the artist’s intentions, concept and meaning of the artwork formed a large part of the research. Combined with this was scientific research into the effectiveness of Tri-ammonium Citrate as an aqueous surface cleaning agent and analysing construction of 3-Dimensional artworks.